PEMBERDAYAAN PEREMPUAN DALAM KONTEKS BUDAYA LOKAL: STUDI KASUS PEMANFAATAN LAHAN PEKARANGAN PANGAN LESTARI - Faza Amalia Khusna; Rosnida Sari (Jurnal Analisa Sosiologi, 2024)
Women's empowerment has an important role in development. One of the ways to realize empowerment for women is the Sustainable Food Yard (P2L) program. With this empowerment, the community, especially mothers, can experience changes in their level of knowledge, attitudes and increased welfare. Thus, the community in Wonosobo Village, Banyuwangi Regency has implemented Sustainable Food Farming (P2L) activities through the institution of the Sri Tanjung Women's Farmers Group. Through Sustainable Food Yard (P2L) activities, group members can fulfill their need for vegetables for daily consumption. The women's empowerment carried out by KWT Sri Tanjung is related to tradition because Wonosobo Village really upholds traditional values. Social Capital in cultural relationships is highly correlated. Social norms, social networks, and beliefs are the main factors in tradition. The village clean ritual provides space for women to contribute to the ritual, even though women are always placed in the domestic sphere. The culture in Wonosobo Village provides access for women to become ajen or leaders in the mocoan tradition or reading the lontar book. In the era of modernization there have been changes to the village's clean ritual customs, there are several performances such as jaranan, music and so on. Ider bumi is part of the Osing culture, but in its activities there is a mixture of Javanese culture in it which is not a serious problem, because the two cultures coexist. Traditions and P2L programs go hand in hand, resulting in productive and complementary activities. The type of research used in this research is a qualitative method with a phenomenological approach. To determine informants, purposive sampling was used and data collection was carried out through observation, in-depth interviews and documentation. In testing the validity of the research data, source triangulation was used and for data analysis, namely through data transcript, namely categorization of data in text form the final step is drawing conclusions.